2004
DOI: 10.1111/j.1365-2273.2004.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Otic drops used to clear a blocked grommet: an in vitro prospective randomized controlled study with blinded assessment

Abstract: Clinicians often prescribe otic drops anecdotally to try and clear grommets blocked with blood. We carried out an in vitro double-blind randomized controlled study comparing the efficacy of sodium bicarbonate, Locorten Vioform and olive oil drops in clearing Shah grommets placed in 'artificial ears' and blocked with blood in a standardized fashion. There were 33 grommets in each group, and drops were inserted three times a day for 7 days. Olive oil drops cleared 17 of 33 (51.51%), Locorten Vioform cleared one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…TT blockage has been reported as low as 7% and as high as 25% [4,5]. A study in 1991 reported that approximately 50% of blocked tubes were a result of blood clot from the time of surgery [6]. We have observed postoperative TT blockage secondary to a blood clot to be associated with more bleeding at the time of TT insertion.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…TT blockage has been reported as low as 7% and as high as 25% [4,5]. A study in 1991 reported that approximately 50% of blocked tubes were a result of blood clot from the time of surgery [6]. We have observed postoperative TT blockage secondary to a blood clot to be associated with more bleeding at the time of TT insertion.…”
Section: Introductionmentioning
confidence: 76%
“…Many reasons exist for TTs to become blocked after insertion, and frequent bleeding is a reason for this blockage. This can be attributed to many factors, including inflammation of the middle ear or tympanic membrane, patient coagulation profile, and also surgeon skill and experience [6]. Intraoperative blood clots can lead to significant problems with postoperative TT blockage, and thus may necessitate further treatments and in some instances, a second surgical intervention to replace the TTs.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Various factors have been thought to be responsible in the etiology such as tube diameter, the shedding of epithelial cells, poor surgical technique, and insufficient hemostasis. [20] Although the high viscosity of ear drops containing steroids has been considered to be a cause, there are extremely limited data related to the incidence of tube obstruction associated with ear drops. [13] Samarei [8] compared topical ofloxacin ear drops and ciprofloxacin/ dexamethasone combination and reported the tube obstruction rate to be 5.2% in the ofloxacin group and 6% in the ciprofloxacin/ dexamethasone combination.…”
Section: Discussionmentioning
confidence: 99%